Is the combination of behavioral activation and attention training technique effective to reduce depressive symptomatology? A multiple case study - Krings, Audrey; Geurten, Marie; Lazari, Ecaterina; Blairy, Sylvie (Frontiers in Psychology, 2022)
Background: This study tested whether the combination of BATD and Attention Training Technique (ATT) is effective to reduce depressive symptomatology and investigate the mechanisms of action underlying the effectiveness of treatment with a multiple N-of-1 trials. Methods: Nine adults with depressive symptoms were randomly included in three different combinations of BATD and ATT, concurrent in Condition 1 and sequential in Conditions 2 and 3. The sequential components allow investigating the specific changes that occur during the two distinct treatment phases. Multiple self-report and pre-post assessments were conducted on generic mental health measures (depressive symptoms, life functioning, mood, and well-being) and intervention specific measures (behavioral activation, behavioral avoidance, self-focused attention, cognitive control and rumination), with two-week and three-month follow-up assessments. We also measured treatment adherence with treatment attendance, homework compliance and a clinical interview. Results: Participants’ attendance, homework compliance and satisfaction were acceptable in the three conditions, with higher adherence in Condition 1 and Condition 3. Eight participants out of nine reported a reduction in depressive symptomatology and five an improvement in well-being. Most of their progress was maintained two weeks after the intervention but not three months later. Conditions 1 and 2 seemed to be associated with a higher response to generic mental health measures in comparison to Condition 3. The three conditions were not associated with consistent changes in intervention specific measures, except for rumination with five participants out of nine reporting an improvement in rumination immediately after the intervention and eight participants two weeks after the intervention. The concurrent format was associated with a better improvement in rumination immediately after the intervention. No specific changes of self-focused attention and rumination characterized ATT and no specific changes of behavioral activation, behavioral avoidance and rumination characterized BATD. Conclusions: Our three interventions were judged acceptable and showed positive short-term benefit for generic mental health measures and rumination maintained two weeks later, but not three months later. Results suggest that five sessions of concurrent treatment could be a better option than sequential formats. However, our data did not support the specificity of ATT and BATD treatments.